ICAM1 778G>A (rs1799969), ADD1 1378G>T (rs4961), NPPA 553T>C (rs5065), and NOS3 894G>T (rs1799983) Variants in Infants with Gastroschisis from Western Mexico - Bobadilla Morales, Lucina; Mellín-Sánchez, Estrella Lizbeth; Robledo-Aceves, Mireya; Corona-Rivera, Alfredo; Orozco-Vela, Mireya; Velasco, Juan José Cárdenas-Ruiz; Ramirez-Corona, Juan Antonio; Cruz-Cruz, Jessica Paola; Martínez-Torres, Ana Fátima; Corona-Rivera, Jorge Román (Genetic testing and molecular biomarkers, 2025)
Gene variants of (rs1799969), (rs4961), (rs5065), and (rs1799983) have been proposed as possible genetic risk factors for vascular compromise in gastroschisis. However, this interpretation is questionable because the vascular disruption theory is now considered unlikely. According to current knowledge, gastroschisis is caused by a separation of the umbilical ring. This study reevaluated the gene variants of (rs1799969), (rs4961), (rs5065), and (rs1799983) as potential genetic risk factors for gastroschisis. The study involved a cohort of 151 live-born patients with gastroschisis (cases) and 229 controls from Western Mexico. We used Sanger sequencing to investigate the potential influence of risk alleles for the (rs1799969), (rs4961), (rs5065), and (rs1799983) gene variants. Data were analyzed using logistic regression analysis. The risk of gastroschisis increased in relation to the frequency of homozygosity for the 778G>A (rs1799969) variant among cases and controls (6% vs. 2.6%, respectively, adjusted odds ratio = 3.2, 95% confidence interval 1.0-10.1). For the 1378G>T (rs4961), 553T>C (rs5065), and 894G>T (rs1799983) gene variants, the adjusted odds ratios did not show an association with the risk of gastroschisis. Although the number of identified homozygotes was small, our results suggest that the 778AA (gly241arg) genotype is associated with an increased risk of gastroschisis. This gene variant is discussed in relation to the pathogenesis of amniotic damage in gastroschisis.